2021
DOI: 10.3390/app11178191
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic, Myoelectric, and Aerodynamic Parameters of Euphonic and Dysphonic Voices: A Systematic Review of Clinical Studies

Abstract: Background: At present, there is no clinical consensus on the concept of normal and dysphonic voices. For many years, the establishment of a consensus on the terminology related to normal and pathological voices has been studied, in order to facilitate the communication between professionals in the field of the voice. Aim: systematically review the literature to compare and learn more precisely the measurable and objective characteristics of the acoustic, aerodynamic and surface electromyographic parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For this purpose, the behavior of the extrinsic musculature of the larynx was assessed at the surface electromyographic level during different vocal tasks in men and women with a normal voice. The methodological procedure was based on the results obtained in a recent systematic review of the scientific literature on normal voice [ 18 ]. To the best of our knowledge, no studies have been found in Spanish speakers that analyze normal voice in conjunction with surface electromyography.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the behavior of the extrinsic musculature of the larynx was assessed at the surface electromyographic level during different vocal tasks in men and women with a normal voice. The methodological procedure was based on the results obtained in a recent systematic review of the scientific literature on normal voice [ 18 ]. To the best of our knowledge, no studies have been found in Spanish speakers that analyze normal voice in conjunction with surface electromyography.…”
Section: Discussionmentioning
confidence: 99%